Mobile application for gas order and delivery system / Muhammad Rashid Sulaiman - Sulaiman, Muhammad Rashid (2017)
In today modern standards of living, hydrogen gas has been proclaimed as the crucial substance and widely used as fuels for vehicles, heating our homes, generate electricity and cooking our foods. The manipulation of hydrogen gas has grown to become a propane industry to continue providing hydrogen application to the mankind. One of the significant application of hydrogen gas is cooking gas cylinder which we are often use for cooking in our everyday life. In order to have the cooking gas in our home, some of us buy it from the retailers or order for delivery to their homes. Thus, this project focus on the ordering and delivery of cooking gas to our home. There are underlying problems that may affect the efficiency of the delivery of cooking gas. The stakeholder of this project is a retailer which is Mr.Latiff Aman that provide home delivery service of cooking gas. He faces problems such as trust issue with the driver and problematic management of his sales. The driver also faces difficulties to carry out the delivery job due to improper delivery tracking. Thus, this project is developed to minimize the problems through waterfall approach which consists of requirement gathering, analysis, design and implementation phase. In a conclusion, all the objectives are achieved through the waterfall approach and the prototype of the product is successfully developed. The system architectures involve are mobile devices, internet connection, internet server and a database. In addition, future works are also described which can be added to increase the productivity of the mobile application.